POSŁANIEC WARMIŃSKI” – PISMO DIECEZJI/ARCHIDIECEZJI WARMIŃSKIEJ W LATACH 1982–2010 - Guzewicz, Wojciech (Civitas et Lex, 2015)
Roman Catholic Archdiocese of Warmia is the oldest diocese in the north-eastern Polish. Can boast of many works in the field of pastoral, organizational and material. In the eighties of the twentieth century initiative of major importance not only was the creation of pastoral journal – „Posłaniec Warmiński”. This letter has played a key role in society, not only in the period of Solidarity but until 2010. The well informed about the life of the universal Church and the Archdiocese of Warmia, including its many pastoral initiatives.